2019
DOI: 10.3389/fpls.2019.00858
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Polymer Composition and Spatial Distribution in Ripe Banana and Mango Fruit: Implications for Cell Adhesion and Texture Perception

Abstract: Banana ( Musa acuminata ) and mango ( Mangifera indica ) are two of the most popular fruits eaten worldwide. They both soften during ripening but their textural attributes are markedly different. This study aimed to elucidate the molecular mechanism underpinning textural differences between banana and mango. We used a novel combination of methods at different scales to analyse the surface properties of fruit cells and the potential contribution of cells and cell wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The size of the pore but also its conformation and flexibility govern the diffusion of a molecule through the cell wall. Cells, with intact walls, separated from plant tissues are becoming a popular tool to investigate the permeability of the cell walls and macronutrient digestibility [31][32][33][34][35][36][37][38][39][40][41]. These in vitro studies confirmed that digestive enzymes (α-amylase, proteases and pancreatic lipase) cannot diffuse through the cell wall of many plant-based foods (almond, wheat, chickpea, pea, mung bean, red kidney bean, and sorghum) whereas some cell wall appeared to be more permeable (common bean, potato tuber, banana and mango).…”
Section: Porositymentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the pore but also its conformation and flexibility govern the diffusion of a molecule through the cell wall. Cells, with intact walls, separated from plant tissues are becoming a popular tool to investigate the permeability of the cell walls and macronutrient digestibility [31][32][33][34][35][36][37][38][39][40][41]. These in vitro studies confirmed that digestive enzymes (α-amylase, proteases and pancreatic lipase) cannot diffuse through the cell wall of many plant-based foods (almond, wheat, chickpea, pea, mung bean, red kidney bean, and sorghum) whereas some cell wall appeared to be more permeable (common bean, potato tuber, banana and mango).…”
Section: Porositymentioning
confidence: 99%
“…Particle size reduction also facilitated starch bioaccessibility and digestibility in legumes. Cooking of legumes promoted pectin solubilization, but contrary to fruits and vegetables, this led to cell wall swelling [34] and/or cell separation [70], similarly to cell wall disassembly observed during fruit ripening [40]. Cell walls that remain intact, such as those of separated cells, will prevent or slow down macronutrients digestion (see Section 2.3).…”
Section: Encapsulationmentioning
confidence: 99%
“…Sections were stained with toluidine blue O solution in 0.1 M phosphate buffer (pH 6.8). The samples were observed using an inverted light microscope according to the modified method of Rongkaumpan et al [124].…”
Section: Light Microscopy (Lm)mentioning
confidence: 99%
“…Scanning electron microscopy showed circular depressions with ridge-like features of 80–140 nm in width spaced at 300–350 nm [ 29 ]. Fluorescent imaging also revealed presumed PD connections in other fruits such as bananas and mangoes [ 41 ]. Calcofluor-white staining of cellulose in mature fruits revealed regions between parenchyma cells (PCs) that resemble pit fields in these fruits [ 41 ].…”
Section: Pd Structure and Composition In Fruitsmentioning
confidence: 99%